Managing Multi-Discipline Extended Programmes - Sutherland, Trudy (European Journal of Multidisciplinary Studies, 2022)
The Vaal University of Technology (VUT) has been offering a multidiscipline Extended Programme since 2009 and even though this Programme is made up from different faculties, the entire Extended Programme is overseen by one unit director.Due to the diversity of the unit and the variety of subject offerings, the unit simply cannot follow the same managerial approach that is applied when managing one specific discipline. That is why it requires a completely different and unique approach. The Extended Programme consists of students who are enrolled in different disciplines, i.e. Engineering, Human Sciences, etc., who all learn in different ways and have different needs, but are all managed in one specific unit. Therefore, to ensure that all needs of staff and students are catered for, it is crucial that an alternative managerial approach is applied.The success of a multidiscipline Extended Programme is dependent on the successes of the students, who in return are dependent on the dedication of both academic and administration staff. More so, the positive influence lecturers have on students and the invaluable role they play. It is undeniable that without the guidance and motivation of the lecturers it would be very difficult for the students to succeed. In order for the lecturers to be kept motivated and content, it is important to provide them with equal workloads and ensure transparency at all times. Staff, which is irrefutably guided and kept motivated by a suitable managerial approach. Applying this approach when managing a multidiscipline
Keywords: Extended Programmes, Foundation Programmes, Managing Programmes, Multi-disciplined Programmes1